2020
DOI: 10.1186/s10194-020-01170-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota regulates neuropathic pain: potential mechanisms and therapeutic strategy

Abstract: Neuropathic pain (NP) is a sustained and nonreversible condition characterized by long-term devastating physical and psychological damage. Therefore, it is urgent to identify an effective treatment for NP. Unfortunately, the precise pathogenesis of NP has not been elucidated. Currently, the microbiota-gut-brain axis has drawn increasing attention, and the emerging role of gut microbiota is investigated in numerous diseases including NP. Gut microbiota is considered as a pivotal regulator in immune, neural, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 171 publications
(165 reference statements)
2
62
0
5
Order By: Relevance
“…Dysfunction of this bidirectional communication is involved in numerous diseases of the nervous system, such as Parkinson’s disease, Alzheimer's disease, stroke, multiple sclerosis and spinal cord injury [ 9 13 ]. Additionally, the gut microbiota has been reported to be a pivotal regulator that directly or indirectly mediates the development of neuropathic pain through a complex network of immune, metabolic, endocrine, and neural signalling pathways [ 14 ]. To date, the specific mechanisms underlying gut microbiota-mediated pain progression remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of this bidirectional communication is involved in numerous diseases of the nervous system, such as Parkinson’s disease, Alzheimer's disease, stroke, multiple sclerosis and spinal cord injury [ 9 13 ]. Additionally, the gut microbiota has been reported to be a pivotal regulator that directly or indirectly mediates the development of neuropathic pain through a complex network of immune, metabolic, endocrine, and neural signalling pathways [ 14 ]. To date, the specific mechanisms underlying gut microbiota-mediated pain progression remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota regulates several metabolic and neurological signalling pathways in the host that can be associated with neuropathic pain [ 14 ]. The spinal dorsal horn (SDH) is the primary centre for the processing and transmission of pain perception and plays an essential role in the initiation and maintenance of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…depression and anxiety), 24 , 32 , 33 Parkinson’s disease, 34 increased hypothalamic pituitary adrenal axis (HPA) activity, 35 systemic lupus erythematosus 36 and systemic inflammation. 37 , 38 And, there is a growing appreciation that the gut microbiome may contribute to chronic extra-abdominal pain states, 1 , 3 6 for example in cutaneous inflammatory hyperalgesia 39 and paclitaxel-induced cutaneous thermal and mechanical nociception. 11 However, to the best of our knowledge evaluation of the role of the gut microbiome on skeletal muscle mechanical hyperalgesia has not previously been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing appreciation that the gastrointestinal (gut) microbiome affects the course and severity of many biological processes and diseases, including pain. [1][2][3][4][5][6] Most studies evaluating the role of the gut microbiome in pain have focused on modulation of visceral pain and hypersensitivity (e.g. preclinical models, as well as in inflammatory bowel disease and colitis), [7][8][9][10] and others have shown that the gut microbiome may affect chemotherapy-induced neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…A key role of the intestinal microbiota in the development of inflammatory pain has been detected by measuring the hypernociceptive responses in germ-free and conventional mice [ 138 ]. Recent evidence supports the significant impact of the gut microbiome on neuropathic pain providing the potential for novel therapeutic strategies [ 139 ]. CIPN and the gut microbiome may be linked via the immune-nervous-endocrine axis [ 140 ].…”
Section: Chemotherapy-induced Dysbiosis Associated With Cognitive mentioning
confidence: 99%